0
$\begingroup$

Given any two power series $\sum_{n=0}^{\infty}{a_n{(z\ -\ a)}^n}$ and $\sum_{n=0}^{\infty}{b_n{(z\ -\ b)}^n}$ , if there is some m ∈ N such that $a_n$= $b_n$ for all n ≥ m, then $\sum_{n=0}^{\infty}{a_n{(z\ -\ a)}^n}$ and $\sum_{n=0}^{\infty}{b_n{(z\ -\ b)}^n}$ have the same radius of convergence.

I have found this stated in my book, but it is given without proof and I am unsure as to how this is simply proved.

$\endgroup$
2
$\begingroup$

It's because the radius of convergence is$$\frac1{\limsup_{n\in\mathbb N}\sqrt[n]{\lvert a_n\rvert}}=\frac1{\limsup_{n\in\mathbb N}\sqrt[n]{\lvert b_n\rvert}}$$(since $a_n=b_n$ is $n$ is large enough).


A more basic approach consists in using that fact that, if you have two series $\sum_{n=0}^\infty z_n$ and $\sum_{n=0}^\infty w_n$ and if $z_n=w_n$ if $n$ is large enough, then either both series converge or both series diverge.

$\endgroup$
  • $\begingroup$ Thank you, I think I my troubles were based on not completely understanding what was meant by the limsup, this makes it clear to me :) $\endgroup$ – Suiri Dec 1 '18 at 16:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.